(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the Municipal Basic Sanitation Plan - PMSB of Marabá - PA in a technical way, based on the national guidelines in force. The method used was an exploratory, descriptive research, with a qualitative and quantitative approach made possible by the case study. In the first phase, the bibliographic survey took place by obtaining the most recent version of the PMSB. In the second phase, the diagnostic indicators of the PMSB of Marabá were listed and their classification. To assess the goals, a list of all the monitoring indicators was prepared, and a method for evaluating the pre-existing performance indicators was adapted. In the third phase, the guidelines proposed by a method were adapted, which is a PMSB assessment script. The results allowed to observe the presence of health indicators; epidemiological and socioeconomic factors in the diagnosis of PMSB, but with some database failures. For the list of goals existing in the PMSB, he considered the improvement through PLANSAB indicators. The documented assessment showed that the PMSB is considered red, so it needs immediate updating. It was concluded that the work made it possible to recommend improvements, proposing a more detailed planning and punctuating subsidies for its updating.